Which is Impactful in Nigeria? Investigative or Social Justice Journalism Practice: Evidence from Fisayo Soyombo's Journalism Practice (Journal of Management and Social Sciences, 2023)
Nigeria, as a country in the global south, has media establishments and journalists covering socio-economic and political issues to hold stakeholders accountable. ‘Fisayo Soyombo, an award-winning journalist, reports these issues using investigative and social justice journalism. He recently founded his own media organization to expand his investigative approach in collaboration with other media establishments. Leveraging on background and propositions of media practice model, goal orientationand fraud detection theories, this study examined ‘Fisayo Soyombo’s selected works in investigative and social justice journalism, considering their impact in Nigeria. “Impact” was measured by the attention each selected story received from stakeholders. Data were gathered using Open Profiling of Quality and Content Analysis, with Data Logging, Open Content Categories and Protocols guiding datacollection. Results indicate the potential of these journalism practices for sustainable socio-economic and political development in Nigeria.